Experiences and reflections on the work Society of Tiredness (Research, Society and Development, 2021)
The purpose of this article was to show how Byung-Chul Han's Tiredness Society (2017) was reflected by the master and doctoral students and two teachers, during the time of the pandemic, leading to a broad and in-depth discussion on the family theme. Through comments, the participants, teachers, and students of the academic discipline Family and Subjectivity of the Graduate Program in Family in Contemporary Society at the Catholic University of Salvador-BA, in the first semester of 2021, sought to establish connections and meanings between the content of the work and their own experiences in their specific socio-historical-professional contexts. As Han advocates the existence of a community that doesn't need belonging or kinship, it ended with a discussion of the meaning of family, understood in the context of philosophical, sociological, and psychological ideas.